2011
DOI: 10.5539/ijps.v3n1p50
|View full text |Cite
|
Sign up to set email alerts
|

The Coping Strategies Employed by Female College Athletes after Losing a Game

Abstract: The purpose of this study is to examine the coping strategies employed by university athletes who have lost in a competition. A sample of ten hand ball women athletes (age between 21-24 years old) who represented one of the largest universities in Kuala Lumpur in the Malaysian Inter-varsity games agreed to participate in this study. All of the athletes have signed the consent letter, giving their permission for the interview to be recorded. The result for content analysis has identified two major dimensions; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In any competition, athletes also have to bare in mind that they also have to confront and cope with losing. On the other hand, Omar-Fauzee, Abd-Latif, Tajularipin, Manja and Rattanakoses (2011) found that athletes who lost their game also quest for social support and psychological skills to cope with their emotional frustration. Therefore, the usage of psychological skills including coping strategy of winning or losing, concentration, goal setting, imagery, and self-confidence will helps to raise their motivation in order to maintain their peak performances (Rattanakoses, Omar-Fauzee & Soh, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In any competition, athletes also have to bare in mind that they also have to confront and cope with losing. On the other hand, Omar-Fauzee, Abd-Latif, Tajularipin, Manja and Rattanakoses (2011) found that athletes who lost their game also quest for social support and psychological skills to cope with their emotional frustration. Therefore, the usage of psychological skills including coping strategy of winning or losing, concentration, goal setting, imagery, and self-confidence will helps to raise their motivation in order to maintain their peak performances (Rattanakoses, Omar-Fauzee & Soh, 2009).…”
Section: Introductionmentioning
confidence: 99%